NILAI PENDIDIKAN KARAKTER DALAM 10 PUISI KARYA TAUFIK ISMAIL - Denny Kurniawan; Dinah Lesmanasari; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This is the purpose of describing the value of the character education value in the 10 poems of Taufik Ismail's work: There is a Child Asked on his Father, Prayer, Sea Road, Garden in Central Island Coral, Blood Jacket, Baby Born May 1998, Previous Port Install, About Nurcholis Sergeant, With My Poetry, and Hungry People. This analysis was analyzed by qualitative descriptive techniques Miles and Huberman (Budiyono, 2013, Hlm. 8) with the focus of research on data reduction, analysis and presentation of data, and inference creation. The results show that the values of the educational value of the characters found in Taufik Ismail poetry are religious values, moral values and ethics, hard work values, nationalism values, homeland love values, social values of concern, and values of responsibility.